The assessment of nursing workload in Intensive Care Unit based on the scale "Nine equivalents of nursing manpower use score" (NEMS) - Cudak, Edyta K.; Dyk, Danuta (Nursing Problems / Problemy Pielęgniarstwa, 2007)
Background. An Intensive Care Unit (ICU) is a separate organizational unit whose most important goal is to support a patient’s life functions in a life-threatening condition. Optimal nursing staffing in ICU should satisfy patients’ needs undergoing surgical procedures as well as those receiving preventive treatment. Aim. The purpose of this study was to evaluate nursing workload based on NEMS scale and to compare it with a group of patients undergoing operative procedure and those not requiring surgical intervention. Material and methods. The investigated group comprised all patients admitted to the clinical ICU from July to August 2005. The method used in the study was participant observation with the application of two standardized scales: apache II and NEMS. The research method used was documentation analysis. Results. The study included 80 patients (17 operated - patients and 63 non-operated-patients). The mean age was: 56.6 ± 14.2 for operated - patients and 57.5 ± 19.9 for non-operated-patients. The mean length of stay for surgical patients was 3.1 ± 2.9 days, and for non-surgical patients 11.9 ± 18.4 days. The patient-level score in the surgical group was 25.8 ± 7.3 on day duty and 25.7 ± 6.3 on night duty. In the non-surgical group the mean score was 26.8 ± 7.0 on day duty and 26.4 ± 6.9 on night duty. The mean score of nursing staffing was 6.3 ± 0.7 nurses on day duty and 6.2 ± 0.7 on night duty with mean number of patients on day and night duty: 9.5 ± 1.0 and 9.8 ± 0.9 respectively. Mean nursing workload was 43.9 ± 9.1 points on day duty and 42.5 ± 7.5 points on night duty. Conclusions. No significant statistical differences were noticed in nursing workload between the surgical patients and non-surgical patients. Nursing workload determined by means of NEMS scale is similar to the workload presented by the author of the original methodological tool. Workload is dependent on the clinical condition of the patient.